2013
DOI: 10.1097/gco.0000000000000028
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes

Abstract: It is now generally accepted that, especially in high-risk women, overt diabetes should be excluded at first prenatal visit. However, internationally the debate on the best screening strategy for GDM continues. In most populations the implementation of the IADPSG screening strategy will lead to an important increase in the prevalence of GDM and associated costs and workload. Risk stratification in IADPSG-positive women may reduce over-treatment. Using clinical prediction models may be a more cost-effective alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Using the current screening methods and thresholds in Sweden, this study confirmed this level of GDM. Clearly, the “true level” of GDM within a specific setting depends on screening method (universal/general), the criterion for diagnosis of GDM [22], coverage of OGTT in the targeted population, the OGTT 2-hour cut-off value, and background characteristics of the pregnant population [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Using the current screening methods and thresholds in Sweden, this study confirmed this level of GDM. Clearly, the “true level” of GDM within a specific setting depends on screening method (universal/general), the criterion for diagnosis of GDM [22], coverage of OGTT in the targeted population, the OGTT 2-hour cut-off value, and background characteristics of the pregnant population [23]. …”
Section: Discussionmentioning
confidence: 99%
“…The fasting plasma glucose, insulin level, and HOMA-IR after six weeks of intervention decreased significantly compared to the control group. In that study, GDM diagnosis was based on 75-g glucose OGTT (the new ADA criteria), whereas in our study, 84% of the recruited patients were diagnosed by 100-g glucose OGTT, which detects severe cases of GDM ( 27 ). Another difference is that in Asemi et al study, patients requiring insulin therapy during pregnancy were excluded, whereas in our study, 90% of the patients in group I and 83% in group C required insulin for glycemic control.…”
Section: Discussionmentioning
confidence: 79%
“…It is difficult to compare the prevalence of gestational diabetes mellitus (GDM) in different countries because screening and diagnosis vary widely [3]. A frequently used screening protocol is a two-step procedure including a 50 g glucose screening test (O'Sullivan) followed by a 3-h 100 g oral glu-cose tolerance test (OGTT) if the initial test is positive (Carpenter and Coustan criteria) [4,5].…”
Section: Introductionmentioning
confidence: 99%